The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1080/10408699891274174
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Fermentation and Associated Changes in Physicochemical and Functional Properties

Abstract: Fermentation of cassava is an important processing technique followed in different parts of the world. Although fermentation is known to bring about vast changes in the physicochemical and functional properties of the tubers, attempts have seldom been made to consolidate and critically analyze the available information. Glaring inconsistencies and contradictions noticeable in some of the results reflect the differences and variations in the artisanal processes followed in the preparation of these products. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 0 publications
1
68
0
5
Order By: Relevance
“…On an energy production basis, providing mostly carbohydrate in the form of starch, it ranks fourth after rice, wheat and maize as a food source. 1 The cooking quality of fresh cassava roots is affected by cultivar, age at harvest, cultivation practices and environmental conditions during the growing season. An important complaint from consumers of fresh roots is the time needed to cook some of them and a lack of desirable texture at the end of the cooking time.…”
Section: Introductionmentioning
confidence: 99%
“…On an energy production basis, providing mostly carbohydrate in the form of starch, it ranks fourth after rice, wheat and maize as a food source. 1 The cooking quality of fresh cassava roots is affected by cultivar, age at harvest, cultivation practices and environmental conditions during the growing season. An important complaint from consumers of fresh roots is the time needed to cook some of them and a lack of desirable texture at the end of the cooking time.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava chips fermented with yeast have been shown to have high levels of lysine, glutamic acid, leucine and phenylalanine ( Table 2). In contrast to fermentation with yeast, fermentation of cassava products with fungal inoculum has been shown to result in about 42% reduction in total amino acids [68,76].…”
Section: 6mentioning
confidence: 99%
“…VEGETABLES AND ROOT CROPS have been made in plain water (allowing the influence of the natural microbial flora) and after the addition of microbial inoculums. The influence of soaking on the texture was reviewed comprehensively by Moorthy and Mathew (1998), while the corresponding reduction in cyanogens are overviewed by Padmaja (1995). The latter quotes a study where Bourdoux et al found that soaking roots in water for 1 day decreased the total cyanogenic potential from 108 to 60 mg/kg, while a 5-day treatment resulted in a final content of 3 mg/kg (Padmaja, 1995).…”
Section: Soakingmentioning
confidence: 98%
“…These include "mingao" (fermented starch dissolved in boiling water and flavored with fruits) and "cassareep" or "tucupay" (juice pressed from tubers, with added spices and concentrated) (Balagopalan, 2002), and the fermented alcoholic beverage "carixi" made from a mixture of cassava and sweet potatoes by the Juruna people of Brazil (Santos et al, 2012). An overview of cassava root based food products world-wide may be gained from various reviews (Balagopalan, 2002;Chuzel, 2001;Gnonlonfin et al, 2012;Moorthy and Mathew, 1998;Westby, 2002).…”
Section: Products and Processing-cassava Root Tubersmentioning
confidence: 99%